Investigating Tesl Curriculum Using Tpack For 21st Century Learning Skills: A Case Study In An Institute Of Teacher Education In Malaysia - Quinie Ong, Kooi Loo (2023)
Education 5.0 is about using technology as an enabler to add value and increase effectiveness to improve learning. However, the issue on the poor quality of ICT integration in the teaching of English as a second language still persists. To address this problem, this study investigated the TESL planned curriculum, delivered curriculum and experienced curriculum in an Institute of Teacher Education (ITE) in Malaysia. The main aim of this case study was to investigate the use of Technological Pedagogical Content Knowledge for 21st century learning skills (TPACK21cls) in the curriculum by integrating the SAMR model to gauge the stages of ICT use. Qualitative data methods include document analysis, interviews and reflections while data analysis was based on data reduction into themes through coding processes and final representation of findings. The findings revealed that the planned curriculum emphasised the development of pre-service teachers’ Content Knowledge and Pedagogical Content Knowledge. TPACK21cls was missing in the rationales and learning outcomes of the course summaries. As for the delivered curriculum, the participants were confident with their Technological Knowledge but the knowledge to use ICT to teach in their T&L was mainly learnt by their experiences as students. They applied how they used ICT for their assignments and tutorial tasks into their T&L during practicum. Nevertheless, the lecturers, being digital immigrants, were able to plan tasks using ICT tools at modification stage.